Foreign film in Poland, 1964–1975: selection, import and audience. An introduction - Klejsa, Konrad (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2023)
The topic of this article is part of the broader research project on lm distribution in the People’s Republic of Poland. An important base for this text is the archival resources of the Film Polski Export and Import Company, established in 1964, the year therefore chosen as the starting point of the analysis. The point of departure is 1975, when important changes in the lm import volume occurred. The article comprises of sections dedicated, respectively, to pre-selection of feature films, new releases and lms in circulation. The data on the number of released titles show that in almost the entire period under study, the total number of foreign films from other ‘people’s republics’ was lower in any given calendar year than the number of films from capitalist states. However, the fact that more films from communist countries were imported to Poland did not mean that the former had larger audiences and generated greater revenues.